Curcumin for Upgrading Skin Colour of Broilers - Awang Iskandarzulkarnian, Pengiran Rayari; Ungku Mohsin, Ungku Chulan; Ahmad, Faujan (1992)
Curcumin was mixed in chicken feed at the rate of 1 mg, 10 mg and 100 mg per kilogram of feed and fed to a group of 37 two-week-old Isa-Vedette broiler chicks for three weeks to improve the pigmentation of the skin. The treatment resulted in the development of an attractive yellowish orange coloration of the skin compared to the skin of control birds. Skin colour intensity was noted highest in birds that received 10 mg of curcumin per kilogram of feed and second highest in birds that received 100 mg of the colour rant. The development of fatty liver is seen to correlate with the quantity of curcumin given to the birds.